HIV serologically indeterminate individuals: Future HIV status and risk factors - Mwinnyaa, George; Grabowski, Mary K.; Gray, Ronald H.; Wawer, Maria; Chang, Larry W.; Ssekasanvu, Joseph; Kagaayi, Joseph; Kigozi, Godfrey; Kalibbala, Sarah; Galiwango, Ronald M.; Ndyanabo, Anthony; Serwadda, David; et al. (PLoS ONE, 2020)
Indeterminate HIV test results are common, but little is known about the evolution of indeterminate serology and itssociodemographic and behavioral correlates. We assessed future HIV serological outcomes for individuals with indeterminate results and associated factors in Rakai, Uganda. Methods 115,944 serological results, defined by two enzyme immunoassay (EIAs), among 39,440 individuals aged 15–49 years in the Rakai Community Cohort Study were assessed. Indeterminate results were defined as contradictory EIAs. Modified Poisson regression models with generalized estimating equations were used to assess prevalence ratios (PRs) of subsequent HIV serological outcomes and factors associated with HIV indeterminate results.
Keywords: HIV; Individuals; HIV status